Students Performance in Literature-in-English Exploring Ghanaian students perception of the Influence of Pedagogy on Teaching and learning (Global Journal of Human-Social Science, 2025)
The performance of Literature-in-English students at senior high schools in Ghana has declined. Over the past decade, less than half of the students have passed Literature-in-English, with performance dropping by more than 50% from 2007 to 2021. Pedagogical practices are a key factor influencing students’ results. Removing effective teaching from the process has serious consequences for students’ academic success. This study examined the impact of teaching methods on students’ interest and achievement in Literature-in-English at the senior high school level in Ghana. A descriptive research design was employed, and 601 students were selected using simple random sampling. Data was collected through the Teachers’ Teaching Methods Questionnaire (TTMQ). The findings show that teachers often do not incorporate real-life experiences into their lessons, depriving students of the chance to connect their learning to daily life. Furthermore, teachers tend not to assign challenging tasks or provide relevant reading materials. Students reported that their teachers prioritise examinations over the syllabus content. Teachers focus on preparing students for tests rather than equipping them with lifelong knowledge. The study confirms that teachers’ pedagogical skills can have a significant impact on students’ interest in a subject. It is recommended that Literature-in-English teachers receive regular professional development training in teaching, learning, and assessment methods.